2013
DOI: 10.1093/eurheartj/eht342
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aliskiren on post-discharge outcomes among diabetic and non-diabetic patients hospitalized for heart failure: insights from the ASTRONAUT trial

Abstract: AimsThe objective of the Aliskiren Trial on Acute Heart Failure Outcomes (ASTRONAUT) was to determine whether aliskiren, a direct renin inhibitor, would improve post-discharge outcomes in patients with hospitalization for heart failure (HHF) with reduced ejection fraction. Pre-specified subgroup analyses suggested potential heterogeneity in postdischarge outcomes with aliskiren in patients with and without baseline diabetes mellitus (DM). Methods and resultsASTRONAUT included 953 patients without DM (aliskiren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 21 publications
0
39
0
4
Order By: Relevance
“…In our trial, patients with diabetes had the treatment stopped prematurely because of regulatory concern about the safety of aliskiren added to an ACE inhibitor in such persons. [15][16][17][18][19] Because of this, we revised our statistical analysis plan to prespecify examination of the effect of combination therapy, as compared with enalapril alone, in patients without diabetes. 13 This analysis showed the same effect of combination therapy as in the trial overall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our trial, patients with diabetes had the treatment stopped prematurely because of regulatory concern about the safety of aliskiren added to an ACE inhibitor in such persons. [15][16][17][18][19] Because of this, we revised our statistical analysis plan to prespecify examination of the effect of combination therapy, as compared with enalapril alone, in patients without diabetes. 13 This analysis showed the same effect of combination therapy as in the trial overall.…”
Section: Discussionmentioning
confidence: 99%
“…13 This intervention was based on the findings of possible harm from aliskiren in patients with diabetes in two other trials (ASTRONAUT and ALTITUDE). 15,16,19 Our trial included a large proportion of patients with diabetes, who had exposure to aliskiren for a median of 24 months despite truncated followup. We did not identify worse outcomes in the patients with diabetes who were treated with combination therapy than in those who were treated with enalapril alone.…”
Section: Discussionmentioning
confidence: 99%
“…More complete renin-angiotensin-aldosterone system blockade in certain HF subgroups has been met with excess complications. 28 It was not possible to compare intermediate and high dose or drugs, and similarly, the studies did not randomized patients to low dose versus placebo. We also did not have access to individual participant data for each study, and thus, we could not estimate study-specific hazard ratio unless reported for the study.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of all-cause mortality with aliskiren significantly decreased at 12 months in nondiabetic patients; these same patients experienced less adverse events from aliskiren. 28 A similar adverse event profile of aliskiren in diabetic patients was seen in another trial in patients with type 2 diabetes mellitus and chronic kidney disease, cardiovascular disease, or both. 29 These latter investigators concluded that there was no role for aliskiren in patients with type 2 diabetes mellitus; this caveat is likely applicable to the majority of patients with HF and diabetes mellitus as well.…”
Section: Aliskirenmentioning
confidence: 53%